Study on anti-wear and friction-reducing compounding additives in lithium greases - Yuhai Shen; Yanshuang Wang; Jianghai Lin; Pu Zhang; Xudong Gao; Zijun Wang (Industrial Lubrication and Tribology, 2023)
Purpose This paper aims to determine a suitable anti-wear and friction-reducing compounding additive for lithium greases (LG) by investigating the effects of three single additives potassium borate (PB), zinc dialkyl dithiophosphate and molybdenum dialkyl dithiophosphate (MoDDP) and two compound additives on the friction, wear and extreme pressure properties of LG. Design/methodology/approach The effects of the above five additives on the friction, wear and extreme pressure properties of LG were investigated using an SRV-5 friction tester. An X-ray photoelectron spectrometer was used to analyze the various elements presented on the wear surface as well as the types of compounds. Findings The compound additive suitable for grease consists of PB and MoDDP, which have excellent friction reduction, anti-wear and extreme pressure properties. And a boundary protection film consisting of oxide and MoS 2 is formed on the friction surface, thus improving the friction reduction and anti-wear performance of the grease. Originality/value This study can improve the anti-wear and friction-reduction performance of greases, which is of great importance in the field of industrial lubrication. The results of this paper are expected to be useful to researchers and academics of grease. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-11-2022-0350/